Painting psychosis: an empirical investigation of the self-portraits of Edvard Munch - Bettelheim, Eric C.; Liu, Jingyi; Dazzan, Paola; Turkheimer, Federico (Frontiers in Psychiatry, 2026)
Substantial evidence demonstrates that the brain is more interested in faces than in other subjects and that self-related material, particularly self-images, have higher saliency than non-self-referential material. Studies of self-portraits have revealed correlations between stylistic elements and artists’ states of mind. Edvard Munch, a founder of Expressionism and most famous for “The Scream”, was pre-occupied with depicting his subjective experience and a prolific painter of self-portraits. He has been posthumously diagnosed as suffering from schizophrenia, anxiety, bipolar and other disorders associated with altered perception. Munch’s painted self-portraits were empirically examined to determine if variations in stylistic elements, contrast, colour and fractal dimension, correlate with life events associated with psychopathology. His portraits were also examined as controls and to test whether images of others, related and unrelated to him, vary stylistically from his self-portraits and from each other. Productivity was examined as an independent indicator. Significant changes in contrast, colour, fractal dimension and productivity during critical periods in his life were identified in his self-portraits consistent with the conclusion that Munch is diagnostically best described as suffering from early onset psychosis. Examination of his portraits of related and unrelated people revealed differences from self-portraits and from each other consistent with comorbid social anxiety disorder.